Cortical network modulations associated with prolonged training of the multiple object-tracking task - Felßberg, Anna-Maria; Schönemann, Nadine; Hopf, Jens-Max; Schoenfeld, Mircea Ariel; Merkel, Christian (Imaging neuroscience (Cambridge, Mass.), 2025)
A fundamental mechanism enabling object permanence for the visual system constitutes visual tracking. During the interaction with a dynamic visual environment we are able to continuously track a multitude of objects simultaneously. Early work suggests that this mechanism is subject to improvement under task-specific behavioral training, though exhibiting a limited transferability to other cognitive tasks. Interestingly enough, specific groups of subjects, regularly involved with demanding visual tasks, may possess expertise in the tracking-task, hinting toward long-term perceptual learning processes playing a role in modulating functional networks involved in visual tracking. In order to identify functional networks being susceptible to cortical flexibility during prolonged task-specific performance, thirty-three subjects executed a multiple-object-tracking task over the course of five successive sessions over 2 weeks. During the first and last session, domain-specific location- and object-based representational functional response patterns toward the relevant, attended target objects at the end of the tracking phase were recorded using a 3T Scanner. Differential modulations were observed within two separate functional networks identified previously being involved in encoding the location-based and object-based aspects of the tracking task. During training, parametric, location-based information processing consolidates preferentially within visual cortical areas over time and shifts from an object-based, non-parametric mechanism within frontal control networks.